Integrated Analysis of miRNA-mRNA Expression in Mink Lung Epithelial Cells Infected With Canine Distemper Virus - Chen, Qiang; Tong, Mingwei; Sun, Na; Yang, Yong; Cheng, Yuening; Yi, Li; Wang, Gaili; Cao, Zhigang; Zhao, Quan; Cheng, Shipeng (Frontiers in Veterinary Science, 2022)
Canine distemper (CD) caused by canine distemper virus (CDV) is one of the major infectious diseases in minks, bringing serious economic losses to the mink breeding industry. By an integrated analysis of microRNA (miRNA)-messenger RNA (mRNA), the present study analyzed the changes in the mink transcriptome upon CDV infection in mink lung epithelial cells (Mv. l. Lu cells) for the first time. A total of 4734 differentially expressed mRNAs (2691 upregulated and 2043 downregulated) and 181 differentially expressed miRNAs (152 upregulated and 29 downregulated) were identified. Gene Ontology (GO) enrichment indicated that differentially expressed genes (DEGs) were associated with various biological processes. Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis of the combination of miRNA and mRNA was done for immune and inflammatory responses, such as Janus kinase (JAK)-signal transducer and activator (STAT) signaling pathway and nuclear factor (NF)-kappa B signaling pathway. The enrichment analysis of target mRNA of differentially expressed miRNA revealed that mir-140-5p and mir-378-12 targeted corresponding genes to regulate NF-kappa B signaling pathway. JAK-STAT signaling pathway could be modulated by mir-425-2, mir-139-4, mir-140-6, mir-145-3, mir-140-5p and mir-204-2. This study compared the influence of miRNA-mRNA expression in Mv. l. Lu cells before and after CDV infection by integrated analysis of miRNA-mRNA and analyzed the complex network interaction between virus and host cells. The results can help understand the molecular mechanism of the natural immune response induced by CDV infection in host cells and provide an experimental basis for exploring potential antiviral targets.